Artroplastia de quadril em Minas Gerais : análise dos dados do Sistema Único de Saúde - Maicom Marcio Perigolo Lima (2023)
Introduction: increased longevity is associated with an increase in the incidence and prevalence of chronic diseases, such as arthrosis or osteoarthritis, in addition to increasing the chance of femoral neck fractures, which are more common in older individuals, leading to a consequent increase in the need for of hip arthroplasty surgery. Objective: to analyze the incidence of hip arthroplasties performed by the Unified Health System in Minas Gerais, from 2013 to 2022. Methodology: this is an ecological study in which the units of analysis were the Health Microregions of the state of Minas Gerais. The frequency of different types of hip arthroplasties, their temporal evolution, the average age of completion for each of these procedures (by type) were described, in addition to estimating the annual incidence of surgery. An analysis of factors associated with the incidence of surgery in different microregions was also carried out. The incidence rate in 2018 was considered as an evolution variable. The factors investigated regarding the association in relation to the surgery rate per 100,000 inhabitants were: the Minas Gerais Social Responsibility Index (IMRS); proportion of female inhabitants; percentage of inhabitants over 50 years old; percentage of white inhabitants; specialist doctors from the Brazilian Society of Orthopedics and Traumatology (SBOT)/1,000 inhabitants; and number of beds per Health Macroregion. To analyze the projection between the incidence of arthroplasty and the other study variables, the Spearman projection coefficient was used. A simple and multiple Negative Binomial regression model was used, considering the occurrence of arthroplasty in 2018 as the outcome, and the other study indicators as explanatory variables, including the IMRS Health sub-indices. When selecting the variables for inclusion in the multiple models, if a p-value less than 0.10 as selective. Significant variations at the 5% significance level remained in the final model. Results: from January 2013 to December 2022, 34,273 admissions for hip arthroplasty were identified in Minas Gerais, which represented a rate of 15.5 admissions for surgery per 100 thousand inhabitants. The most frequent types were: uncemented/hybrid primary total hip arthroplasty (36.8%), partial hip arthroplasty (34.8%) and cemented primary total hip arthroplasty (17.3%), respectively. Regarding temporal evolution, the median surgery incidence values remained almost constant between the years 2013 and 2018, with an increase in 2019. In 2020 the median reached the lowest value of the trained period, increasing in 2021 and reaching the highest value of the historical sample trained in 2022. The results of the multiple models revealed that the factors that occurred associated with the increase in the incidence of arthroplasty were higher IMRS Education and a higher proportion of people aged 50 or over. Conclusion: it can be concluded that in regions with a better population education situation there is possibly more access to hip arthroplasty and that older populations have a greater need for surgery.